Improving the Management of the Mountain Payung Tourism Area, Facing Post Pandemic Situation - Fandi Ahmad; Laksmi Fitriani (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Coronavirus has caused almost all businesses to experience a slump, including tourism and other related businesses, the policy of limiting activities and closing public facilities has resulted in the visit rate dropping drastically to zero, this makes the tourism sector seem dead, and has a domino effect on other businesses. However, along with the current declining number of transmission rates in Indonesia, it must be responded to as a new opportunity, This study tries to provide suggestions in order to prepare the human resources contained in the management of tourism object management to be prepared to welcome the explosion of visitors, so that they can provide excellent service and create a competitive advantage. Design/methodology/approach: In this study we used a descriptive qualitative approach which tried to conduct interviews with related parties such as village heads, Perhutani and local residents whose areas were affected by the impact of Covid 19 by focusing on the mount Payung ecotourism area in Magelang, Central Java, and the results of this study are proposals, especially in preparing human resources to be more optimal in managing tourist attractions. Findings: From the results of the study, it is known that some infrastructures are not maintained and tend to be neglected due to the lack of a workforce that manages these tourist attractions coupled with budget constraints, because so far they have only relied on assistance from the central government, therefore collaboration from each element is needed which is then supported by formulation of sustainable business processes so as to create independence so that they do not only depend on the government in managing tourist attractions. Research limitations/implications: The locus of this research is only limited to the results of observations made at Mount Payung Magelang Practical implications: the results of this study can be used as a reference to develop human resources in managing tourism areas optimally Originality/value: This paper is original. Paper type: Research paper